2020
DOI: 10.1002/jdd.12412
|View full text |Cite
|
Sign up to set email alerts
|

Developing a curriculum blueprint and taxonomy: Process, progress, and pivots

Abstract: Curriculum transformations represent opportunities to innovate; however, there are few examples to inform this process. In 2018, the University of North Carolina at Chapel Hill (UNC) Adams School of Dentistry began to transform the predoctoral curriculum to improve content integration, enhance team‐based experiences, and develop leaders. Part of this experience has been crafting a conceptual curriculum guide or “blueprint” that outlines a vision for the design process and ensures the transformation achieves it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…To construct the outcomes, the team assembled a list of all possible outcomes desired for a learner, including the relevant knowledge for current and future practice, the tasks learners should be able to perform, and the values and attitudes we hope to cultivate. In addition, we sought inspiration from research conducted at other dental schools and published examples in health professions education 4,10 . This synthesis resulted in the CARE framework, a model similar to CanMEDS, 11 that orients program outcomes around four key roles the graduate is expected to embody: Clinician : A knowledgeable and skillful provider of high‐quality and safe patient‐centered care. Advocate : A positive influencer of health for diverse patient populations and communities. Researcher : A scholar committed to continuous learning necessary for practice and development. Entrepreneur : An innovator who contributes to exceptional and novel service experiences. …”
Section: Discussionmentioning
confidence: 99%
“…To construct the outcomes, the team assembled a list of all possible outcomes desired for a learner, including the relevant knowledge for current and future practice, the tasks learners should be able to perform, and the values and attitudes we hope to cultivate. In addition, we sought inspiration from research conducted at other dental schools and published examples in health professions education 4,10 . This synthesis resulted in the CARE framework, a model similar to CanMEDS, 11 that orients program outcomes around four key roles the graduate is expected to embody: Clinician : A knowledgeable and skillful provider of high‐quality and safe patient‐centered care. Advocate : A positive influencer of health for diverse patient populations and communities. Researcher : A scholar committed to continuous learning necessary for practice and development. Entrepreneur : An innovator who contributes to exceptional and novel service experiences. …”
Section: Discussionmentioning
confidence: 99%
“…The curriculum transformation at the University of North Carolina Adams School of Dentistry served as the inspiration for conducting the intervention with incoming predoctoral dental students about psychological safety. 20 One prominent aspect of the Advocate, Clinician, Thinker…”
Section: Methodsmentioning
confidence: 99%
“…The curriculum transformation at the University of North Carolina Adams School of Dentistry served as the inspiration for conducting the intervention with incoming predoctoral dental students about psychological safety 20 . One prominent aspect of the Advocate, Clinician, Thinker Curriculum is to introduce learners to important social and behavioral topics during their initial orientation into the school 21 .…”
Section: Methodsmentioning
confidence: 99%
“…The UNC Adams School of Dentistry is conducting a transformative curriculum redesign, referred to as the Advocate, Clinician, Thinker Curriculum 24,27 . Early research conducted by the School identified faculty support as a primary concern for an effective transition; therefore, the Dean committed to establishing the ASC to assist faculty during the curriculum change and to sustain the new curriculum moving forward 18 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, curricula change initiatives must remain adaptive to emergent challenges, such as the adoption of an Integrated National Board and the novel coronavirus (COVID‐19) pandemic 19–23 . Several institutions have shared their successes and stumbling points encountered, recognizing multiple approaches to the process 14,15,24 . Of note, documentation and formal evaluation of curriculum change processes also remain a low priority.…”
Section: Introductionmentioning
confidence: 99%